ent-Kaurane Diterpenoids from Croton tonkinensis Induce Apoptosis in Colorectal Cancer Cells through the Phosphorylation of JNK Mediated by Reactive Oxygen Species and Dual-Specificity JNK Kinase MKK4 - Thien Thuong, Phuong; Minh Khoi, Nguyen; Ohta, Saho; Shiota, Shinichiro; Kanta, Hironori; Takeuchi, Kenji; Ito, Fumiaki (Anti-Cancer Agents in Medicinal Chemistry, 2014)
To search for new chemotherapeutic agents to treat colorectal cancer, we isolated a number of natural ent-kaurane diterpenoids from the plant Croton tonkinensis. Among them, only CeKDs with the 15-oxo-16-ene moiety induced the apoptosis of colorectal cancer cell lines Caco-2 and LS180. The active CeKD induced the activation of ERK and JNK, but the inactive ones induced that of ERK, but not that of JNK. It thus appears that JNK seemed to play an important role in the apoptotic activity of the active compounds. The dualspecificity JNK kinase MKK4 was activated in both colorectal cancer cells treated with the active CeKD, but MKK7 was not activated. Further, the active CeKD, but not the inactive one, enhanced the generation of intracellular reactive oxygen species (ROS) in both cells. CeKD-induced cell apoptosis and ROS generation, as well as JNK activation, were inhibited by the antioxidant N-acetyl-L-cysteine. These findings suggest that ROS stimulated the phosphorylation of JNK mediated by MKK4 and played a critical role in CeKD-induced apoptosis in colorectal cancer cells.
Keywords: Colon cancer